The Effect of Tonsillectomy Alone in Adult Obstructive Sleep Apnea. (27th March 2015) - Senchak, Andrew J.; McKinlay, Alex J.; Acevedo, Jason; Swain, Brenda; Tiu, Maitram Christine; Chen, Brian S.; Robitschek, Jon; Ruhl, Douglas S.; Williams, Lawrence L.; Camacho, Macario; Frey, William C.; O'Connor, Peter D.
Abstract : Objective: The purpose of this study was to determine the effect of tonsillectomy as a single procedure in the treatment of adult obstructive sleep apnea (OSA). Study Design: Prospective multi‐institutional study evaluating adults with tonsillar hypertrophy scheduled to undergo tonsillectomy as an isolated surgery. Setting: Tertiary care medical centers within the US Department of Defense. Subjects and Methods: Adult subjects with tonsillar hypertrophy who were already scheduled for tonsillectomy were enrolled from October 2010 to July 2013. Subjects underwent physical examination, Epworth Sleepiness Scale, Berlin Questionnaire, and polysomnogram before surgery and after. Collected data included demographics, questionnaire scores, apnea‐hypopnea index (AHI), and lowest saturation of oxygen. Results: A total of 202 consecutive subjects undergoing tonsillectomy were enrolled. The final analysis included 19 subjects testing positive for OSA. The mean age was 27.9 years; mean body mass index, 29.6; median tonsil size, 3; and most frequent Friedman stage, 1. The AHI before surgery ranged from 5.4 to 56.4 events per hour. The mean AHI decreased from 18.0 to 3.2 events per hour after surgery, a reduction of 82%. The responder rate—with subjects achieving at least a 50% reduction of AHI to a value <15—was 94.7%. Following tonsillectomy, there were statistically significant reductions in median lowest saturation of oxygen level and Epworth Sleepiness Scale and Berlin scores. Conclusions: Adult tonsillectomy alone has beneficial effect in OSA management, particularly in young overweight men with large tonsils, moderate OSA, and low Friedman stage.